Aspects Oriented Programming as a New Approach to Software Engineering - Hołub, Cezary; Owoc, Mieczysław L. (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
The main goal of this article is to present new technology software engineering which expands Object Oriented Programming. This technology is called Aspect Oriented Programming (AOP). In general aspect programming is a paradigm of software engineering which assists the separation of concerns and helps to divide software in independent functional parts. This approach gave us better business requirements mapping development phase in software. Gregor Kiczales and his team at Xerox Corporation originated the concept of AOP in 1996. This team also developed the first and most popular AOP language, AspectJ in 2001. AOP was introduced to address crosscutting concerns such as security, logging, persistence, debugging, tracing, distribution, performance monitoring, and exception handling in a more effective manner. Unlike conventional development techniques, which scatter the implementation of each concern into multiple classes, aspect-oriented programming localizes them. AOP attempts to aid programmers in the separation of concerns, specifically cross-cutting concerns, as an advance in modularization. AOP improves the modularity of programmes, making the code much closer to the design. It can dramatically reduce the time taken to implement common features and functions, improve quality, and integrate old solutions with our product. AOP can give us better and cheaper computer systems. Such IT solutions are needed for the growing information society. Specific to this kind of society is the central position information technology has for production, economy, and society at large. Information technology AOP's core idea is to separating the business logic in an application from the common services that support it. Aspect programming will be probably so important technology as object programming is now.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 8, s. 71-80